MENINGKATKAN KOMPETENSI GURU DALAM PENGGUNAAN BAHAN AJAR MELALUI SUPERVISI AKADEMIK - ., zaharni (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2019)
The use of teaching materials by teachers in educational units aims to make the learning process run well. The purpose of this study was to determine the improvement of teacher competencies in the use of teaching materials through academic supervision in SMK 1 Peureulak Timur even semester 2017/2018 Academic Year. This research was designed in the form of School Action Research which was planned to be carried out in two cycles, as 28 subjects were teachers at SMK 1 Peureulak Timur, where the researcher was the Head of the Peureulak Timur 1 Vocational High School. The results of the teacher's research that competency values ??in the use of teaching materials 91-100 or category A in the initial conditions did not exist, in the first cycle as many as 5 people or 17.86%, while in the second cycle increased to 9 teachers or 32.14%. In the initial conditions there were 3 teachers or 10.71% of the number of teachers having a value between 76-90% with the category Good (B), in the first cycle there were 12 teachers or 42.86% of the total teachers had a value between 76-90 % with the Good category (B), while in the second cycle it increased to 18 teachers or 64.29% of the total teachers. In the initial conditions there were 6 teachers or 21.43% with a value of 60-75 in the category of Enough (C), while in the first cycle there were 7 teachers or 25.00% of the total number of teachers with a value of 60-75 with Enough categories ( C), while in cycle II there is only 1 teacher with a value of 60-75 in the Enough (C) category. In the initial conditions there were 19 teachers or 67.86% of all teachers with the value of the Less category (D), while in the first cycle there were 4 teachers or 14.29% of the number of teachers with the value of category D and cycle II the number of teachers with grades The Less (D) category also no longer exists